Subject-verb dependency formation and semantic interference in native and non-native language comprehension - Fujita, Hiroki; Cunnings, Ian (Applied psycholinguistics, 2024)
Differences between native (L1) and non-native (L2) comprehension have been debated. This study explores whether a source of potential L1/L2 differences lies in susceptibility to memory-based interference during dependency formation. Interference effects are known to occur in sentences like The key to the cabinets were rusty , where ungrammaticality results from a number mismatch between the sentence subject and verb. Such sentences are sometimes misperceived as grammatical due to the presence of a number-matching “distractor” (“the cabinets”). Interference has been well-examined in a number agreement. However, whether and how forming thematic relations is susceptible to interference remains underexplored in L1 and L2 language comprehension. In six preregistered experiments, we investigated semantic interference in language comprehension and explored whether potential L1/L2 differences can be attributed to different degrees of susceptibility to interference. The results did not show that L2 speakers are more susceptible to interference than L1 speakers. Also, the observed interference patterns were only partially consistent with existing theories of memory retrieval during comprehension. We discuss how these theories may be reconciled with our findings and argue our results suggest that similar processes are involved in L1 and L2 subject-verb dependency formation.